TP73‐AS1 promotes breast cancer cell proliferation through miR‐200a‐mediated TFAM inhibition. Issue 1 (5th October 2017) - Yao, Jia; Xu, Feng; Zhang, Danhua; Yi, Wenjun; Chen, Xianyu; Chen, Gannong; Zhou, Enxiang
Abstract: P73 antisense RNA 1T (TP73‐AS1 or PDAM) is a long non‐coding RNA, which can regulate apoptosis through regulation of p53 signaling‐related anti‐apoptotic genes. An abnormal change of TP73‐AS1 expression was noticed in cancers. The effects of TP73‐AS1 in breast cancer (BC) growth and the underlying mechanism remain unclear so far. In the present study, the effect of TP73‐AS1 in BC cell lines and clinical tumor samples was detected so as to reveal its role and function. In the present study, TP73‐AS1 was specifically upregulated in BC tissues and BC cell lines and was correlated to a poorer prognosis in patients with BC. TP73‐AS1 knocking down suppressed human BC cell proliferation in vitro through regulation of TFAM. In our previous study, we demonstrated that miR‐200a inhibits BC cell proliferation through targeting TFAM; here we revealed that TP73‐AS1 could regulate miR‐200a through direct targeting. Moreover, TP73‐AS1 might compete with TFAM for miR‐200a binding thus to promote TFAM expression. Data from the present study revealed that TP73‐AS1 promoted BC cell proliferation through acting as a competing endogenous RNA (ceRNA) by sponging miR‐200a. In conclusion, we regarded TP73‐AS1 as an oncogenic lncRNA promoting BC cell proliferation and a potential target for human BC treatment. Abstract : TP73‐AS1 plays an important role in the regulation of breast cancer cell proliferation by functioning as a ceRNA to regulate the expression of TFAM by inhibiting miR‐200a.